Yes we can! : improving urban schools through innovative education reform - Howell, Leanne; Lewis, Chance W.; Carter, Norvella (Emerald Publishing Limited : Information Age Publishing, 2011)
Yes We Can: Improving Urban Schools through Innovative Educational Reform is a empirically-based book on urban education reform to not only proclaim that hope is alive for urban schools, but to also produce a body of literature that examines current practices and then offer practical implications for all involved in this arduous task. This book is filled with real-world strategies to implement in your quest to inspire and bring about reform. Additionally, we hope that you garner hope from the school personnel, school campuses, and school resources used as examples within the body of this work.We offer this book to all stakeholders who find themselves associated with urban schools: teachers, administrators, parents and even students. Consider this book an empirically based roadmap as you consider being a part of this transformation. We hope that it not only inspire you to adopt the"Yes We Can" spirit, but also empower you to be the beacon of light for urban students whose very future relies on people like you to keep the torch alive.